Pocket Criminal Code 1977: Implications for Counsellors - Eberlein, Larry (Canadian Journal of Counselling and Psychotherapy, 2012)
Counselling in good faith requires a knowledge of both the ethical and legal requirements that affect the counselling process. This article highlights sections of the Criminal Code of Canada and related federal legislation that directly influence thework of mental health professionals — particularly school counsellors. Potential trouble spots are identified to provide the counsellor with a factual basis for helping clients, and to warn the counsellor of ways he could become personally involved inthe process of the criminal justice system. Suggestions are made to assist the counsellor in meeting his responsibilities in a manner consistent with his legal andethical duties.